Investigation of wear mechanics and behaviour of NiCr metallic foam abradables. (May 2022) - Liu, Allan; Marshall, Matthew; Rahimov, Eldar; Panizo, Julian
Current aero-engine sealing materials are reaching their operating limit, as manufacturers seek more efficient engines with longer service lives. Even when utilised in optimum conditions, current materials have inconsistencies in performance due to variabilities in their microstructure, which lead to undesirable responses and events. As such, a new generation of sealing materials is required. Metallic foams are one such material, given the opportunities that exist to both engineer material properties, and achieve relatively consistent microstructures when compared to the current class of thermally sprayed abradable materials. In this study, the abradability of a nickel (70%)–chromium (30%) (NiCr) alloy foam is investigated, with the role of cell size and filler material considered. Tests are performed on a representative high-speed test rig, where a flat blade is used to simulate an aero-engine incursion event. A series of in situ measurement techniques, such as force, temperature and stroboscopic wear measurements are used to characterise the incursion, with DIC (Digital Image Correlation) techniques also employed to investigate breakdown of the foam. Unfilled foams were shown to lead to high blade wear, with the inclusion of filler materials leading to load transfer and collapse of the foam away from the incursion site, along with improved fracture. Both load transfer and ligament collapse mechanisms were found to promote more favourable rub mechanics at all incursion rates tested.